Implementation Indonesian Language Learning through Critical Discourse Analysis of Verbal Abuse in the 2019 Presidential Election - Jumadi Jumadi; Muhammad Rafiek; Rusma Noortyani; Mutiani Mutiani; Ersis Warmansyah Abbas (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe the sources of critical discourse analysis of verbal abuse through social media during the 2019 presidential election of the Republic of Indonesia into Indonesian language learning. This is intended so that students have space to improve critical thinking skills. A qualitative approach with phenomenological methods is used in describing the results of the study. This research has two stages, namely: first, analyzing critical discourse on social media during the 2019 presidential election, and researchers implementing it in Indonesian language learning in universities. Collecting data using observation, interview, and documentation techniques. The results of the study describe that 2019 was a big event for Indonesia. As for the Indonesian presidential candidates in 2019, there are two people, namely; Ir. Joko Widodo (sequence 1) and Prabowo Subianto (sequence number 2). Social media is busy spreading news without any filtering of the information. Based on the reduction of documentation data, it was found that verbal abuse that occurred during the 2019 presidential election of the Republic of Indonesia, namely; a) insulting; b) condescending; c) accusing; and d) expel/dismiss. The practice of learning critical discourse analysis in verbal abuse in the 2019 Indonesian republican elections was held on 7 and 14 October 2021. The topic of learning was reading and writing literacy. Learning is presented by applying the cooperative learning model to see how students are able to express opinions